Bridging the gap: The integration of eDNA techniques and traditional sampling in fish diversity analysis - Wang, Biao; Jiao, Li; Ni, Lili; Wang, Miao; You, Ping (Frontiers in Marine Science, 2024)
In this investigation, we orchestrated a comparative discourse on fish diversity and distribution across 29 strategic sampling points within the rivers of the Changqing Nature Reserve, central China, employing both environmental DNA (eDNA) techniques and conventional sampling methodologies.Our study rigorously identified a total of 46 unique fish species inhabiting the sampled region. Among these, eDNA methods revealed the existence of 34 species, whereas traditional survey techniques unveiled 22 species. Importantly, our results showed that eDNA methods surpassed traditional sampling in terms of alpha diversity, identifying a broader range of species within individual sampling points. 10 species were corroborated by both detection methodologies.Traditional survey methods exclusively identified 12 species that were not detected by eDNA analysis. Conversely, eDNA methods uniquely detected an additional 24 species that remained undetected by traditional surveys. Overall, eDNA analysis demonstrated superior proficiency in capturing a more comprehensive diversity of fish species. A meticulous examination of fish species distribution and relative abundance at individual sampling points revealed discernible discrepancies in species' relative abundance estimation between the two methodologies. Notably, traditional sampling typically rendered higher values of the Shannon diversity index. Moreover, we employed two β-diversity indices -Bray-Curtis and Jaccard -to appraise fish species diversity, and instigated preliminary non-metric multidimensional scaling (NMDS) and principal coordinates analysis (PCoA) to delve deeper into the potential variances between these sampling paradigms. Statistical insights suggested that notwithstanding the nuanced differences in biodiversity measurement between eDNA and traditional sampling, from a statistical vantage, no significant discrepancies were unveiled in measuring riverine fish biodiversity. This inference posits that albeit the divergent capabilities of these sampling methods in encapsulating biodiversity, the technical distinctions in sample processing or biodiversity measurement did not engender significant divergences in statistical outcomes. While eDNA sampling manifested advantages in certain realms, it did not markedly transcend traditional sampling methods. Therefore, we integrate the two methods to bridge the gap between the two approaches. The results demonstrate a more comprehensive and precise assessment of riverine biodiversity through this synergistic analytical framework. The integrated methodology enriches species detection and unveils nuanced understanding of species distribution and relative abundance across different locales.